2014
DOI: 10.1155/2014/506216
|View full text |Cite
|
Sign up to set email alerts
|

Material Selection for Dye Sensitized Solar Cells Using Multiple Attribute Decision Making Approach

Abstract: Dye sensitized solar cells (DSCs) provide a potential alternative to conventional p-n junction photovoltaic devices. The semiconductor thin film plays a crucial role in the working of DSC. This paper aims at formulating a process for the selection of optimum semiconductor material for nanostructured thin film using multiple attribute decision making (MADM) approach. Various possible available semiconducting materials and their properties like band gap, cost, mobility, rate of electron injection, and static die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The results of research that have been carried out on the performance of DSSC solar cells from papaya leaf chlorophyll, the highest efficiency was obtained at the grain size of the substrate ITO 44.46, namely 0.00071% [24]. 7 research flow, which is as above.…”
Section: Literature Reviewmentioning
confidence: 77%
See 1 more Smart Citation
“…The results of research that have been carried out on the performance of DSSC solar cells from papaya leaf chlorophyll, the highest efficiency was obtained at the grain size of the substrate ITO 44.46, namely 0.00071% [24]. 7 research flow, which is as above.…”
Section: Literature Reviewmentioning
confidence: 77%
“…ITO grain size associated with TiO2 grains can be diffused in the ITO grain gap. The results revealed that TiO2 is the best semiconductor material for applications in DSSC and its efficiency is related to its properties such as band gap, electron mobility, electron injection rate, and static dielectric constant [24]. Semiconductor thin layers play an important role in the work of DSSC.…”
Section: Figure 10 Ito Thin Layer Xrd Resultsmentioning
confidence: 99%
“…They claimed that DC classifiers attain the best accuracy of 98%, whereas the DT shows the least accuracy of 84%. These models are also used to predict the best suitable material for designing a solar cell, 79 the optimum range of wavelength of sunlight, temperature, and humidity to obtain the highest efficiency of a solar cell. As per the discussion given in, 80 ANN reports better accuracy than the statistical, conventional, linear, non‐linear, and fuzzy logic models.…”
Section: Role Of Ann In Designing Dsscmentioning
confidence: 99%
“…Chakrabotry et al [13] investigated the influence of characteristics loading on the ranking effectiveness of three frequently used MCDM techniques and concluded that the most important criteria with the greatest weight and higher influence on material selection outcomes. Baghel et al [14] utilized the MCDM for selecting the suitable material for Dye-Sensitized Solar Cells and suggested that the most essential performance factors for a semi-conductor material in DSCs are the budget, static dielectric constant, mobility, band gap and electron injection rate. Zhao et al [15] used GRA and AHP to develop a material selection analytical framework in the context of green design.…”
Section: Bakground Literaturementioning
confidence: 99%